Barry Trotter and the unnecessary sequel - "Gerber, Michael" (London, 2004)
Barry Trotter saved the Hogwash school for Wizards from the unwelcome attentions of Hollywood in BARRY TROTTER AND THE SHAMELESS PARODY. But things move on. Barry and Ermine Cringer have got married and have had two relatively delightful children. Their eldest is a skilled magician. But the youngest doesn't seem to possess any ability at all. Have Barry and Ermine given birth to a Muddle?
Keywords: Psychology